Common hemoglobin variants affecting the diagnosis of β-thalassemia: A large cohort data at a single center - Kritsada Singha; Hataichanok Srivorakun; Supawadee Yamsri; Attawut Chaibunruang; Anupong Pansuwan; Yossombat Changtrakul; Kanokwan Sanchisuriya; Goonnapa Fucharoen; Supan Fucharoen (PLoS ONE, 2026)
Background Many globin chain variants were interpreted as β-thalassemia or hereditary persistence of fetal hemoglobin (HPFH) at routine investigation. We described this in a large cohort of Thai subjects. Methods Hematological data of 43,414 subjects encountered at our thalassemia diagnostic center from January 2013 to July 2025 were reviewed. A total of 372 subjects with hemoglobin (Hb) variants were selectively recruited with leftover DNA specimens for further analysis. Hb analysis was done using high-performance liquid chromatography (HPLC) or capillary electrophoresis. β-globin gene mutations were identified using PCR and related techniques. Results Among 372 subjects recruited, a total of 21 different Hb variants were found. The levels of Hb A 2 , Hb F, Hb variants, and DNA diagnostic requests were recorded. Hb variants with normal Hb A 2 and Hb F levels were requested for β-thalassemia or HPFH in 12.3% (95% CI = 7.9–16.8). This error was increased in Hb variants with Hb A 2 ≥ 3.6% [50.6% (95% CI = 39.8–61.4) and odds ratio of 7.3 (3.6–13.8)] and Hb F ≥ 5.0% [52.2% (95% CI = 37.7–66.6) and odds ratio of 7.8 (3.6–16.7)], especially in those with Hb A 2 ≥ 3.6% and Hb F ≥ 5.0% [71.9% (95% CI = 56.3–87.5) and odds ratio of 18.2 (7.1–48.9)]. Hbs Hope, Tak, Cook, C, Lepore, and Q-Thailand were found to be associated with high proportions of the error. Conclusions Hb variants with increased Hb A 2 levels and/or co-migration with Hb F are associated with a high proportion of mis-interpretation of β-thalassemia in routine practice. Combining Hb analysis using two different methods, and molecular analysis should help improve laboratory interpretation of the cases.